Footprinting of mammalian promoters: use of a CpG DNA methyltransferase revealing nucleosome positions at a single molecule level - Fatemi, Mehrnaz (Oxford University Press, 2005)
Promoters are molecular ‘modules’, which are controlled as individual entities yet are often analyzed by nuclease digestion methodologies which, a priori, destroy this modularity. About 40% of mammalian genes contain CpG islands in their promoters and exonic regions, which are normally unmethylated. We developed a footprinting strategy to map the chromatin structure at unmethylated CpG islands by treatment of isolated nuclei with the CpG-specific DNA methyltransferase SssI (M.SssI), followed by genomic bisulfite sequencing of individual progeny DNA molecules. This gave single molecule resolution over the promoter region and allowed for the physical linkage between binding sites on individual promoter molecules to be maintained. Comparison of the p16 promoters in two human cell lines, J82 and LD419, expressing the p16 gene at 25-fold different levels showed that the two cell lines contain remarkably different, heterogeneously positioned nucleosomes over the promoter region, which were not distinguishable by standard methods using nucleases. Our high resolution approach gives a ‘digitized’ visualization of each promoter providing information regarding nucleosome occupancy and may be utilized to define transcription factor binding and chromatin remodeling.